Pengaruh sampah rumah tangga terhadap lingkungan - Ramadani, Sofi Ramadani (Maliki Interdisciplinary Journal, 2025)
Household waste is a critical environmental issue because improper management can lead to soil, water, and air pollution. Such pollution directly affects ecosystem quality and human health. This article discusses two main types of household waste—organic and inorganic—and their different risks of contamination. Organic waste, if unmanaged, can produce odor and harmful gases, while inorganic waste such as plastics may take hundreds of years to decompose, worsening environmental degradation. Proposed solutions include applying the 3R principles (Reduce, Reuse, Recycle), separating waste at the household level, and reusing waste through composting and recycling. The findings emphasize that effective waste management requires active community participation, continuous public education, government policy support, and technological innovation. With these strategies, the negative impact of household waste can be minimized and environmental sustainability better preserved.